Aquamarine from Thach Khoan Mining Area in Phu Tho Province, Vietnam - Duong, Ly Thuy; Huong, Le Thi Thu (VNU Journal of Science: Earth and Environmental Sciences, 2017)
Aquamarine is a kind of gemstone having attractive color, valuable and being a potential material in gemological industry. In Vietnam, Thach Khoan area has become a noticeable location to explore aquamarine. However, the researches of aquamarine are still limited. Therefore, this study was conducted to determine the characteristics of aquamarine. Eight aquamarine samples from granitic pegmatites in Thach Khoan commune, Thanh Son District, Phu Tho Province were investigated by classical gemological methods, Electron Probe Micro-analysis (EMPA) and Laser Ablation – Inductively Coupled Plasma – Mass Spectrometry (LA-ICP-MS) methods, Raman and Fourier transform infrared (FTIR) spectroscopy. Results showed that aquamarine presents a low concentration of alkali and high amount of iron. Raman and IR spectroscopy indicate the vibrations of specific bonds including Si-O, Al-O, Be-O, the presence of CO 2 and type I H 2 O in structural channels. By dint of that, we are going to study the potential treatment methods of aquamarine in Vietnam in the following study to enhance its quality as well as value in the global market. Keywords Aquamarine, Electron Probe Micro-analysis (EMPA), Electron Probe Micro-analysis (EMPA), Raman spectroscopy. References [1] Tran Anh Ngoan, Characteristics of endogenic mineralizations in the Thạch Khoán – Ba Vì area (in Vietnamese), Journal of Geology, (2002). [2] J. T. David, Mineralogical and geochemical study of the true blue aquamarine showing, shark property, souhtern Yukon territory,Thesis of Master of Science, The University of Bristish Columbia, 2005. [3] J. Fukida and K. Shinoda, Coordination of water molecules with Na cations in a beryl channel as determined by polarized IR spectroscopy, Physics and Chemistry of minerals, 35 (2008) 347. [4] L. T.T. Huong, W. Hofmeister, T. Häger, N. N. Khoi., N. T. Nhung, W. Atichat and V. Pisutha-Arnond, Aquamarine from Thuong Xuan district, Thanh Hoa province, Gem & Gemology, 47 (2011) 42. [5] P. V. Long, G. Giuliani, V. Garnier and D. Ohnenstetter, Gemstones in Vietnam: A review, Australian Gemmologist, 22 (2004) 162. [6] http://idm.gov.vn/nguon_luc/Xuat_ban/Anpham/Tracuu_PVDC/A3.htm#Ailaoshan_SongHong [7] Le Thac Xinh, Metallogeny of the Hoang Lien Son subduction zone, GEOSEA V Proceedings, 2 (1986) 525. [8] http://webmineral.com/data/Beryl.shtml#.VW4sR3M2XBY [9] I. Adamo, A. Pavese,L. Prosperi, V. Diella, D. Ajo, G.D. Gatta and. C.P. Smith, Aquamarine, Maxixe-type beryl, and hydrothermal synthetic blue beryl: Analysis and identification, Gem and Gemology, 44 (2008) 214. [10] I. M. Rudolf and S. Z. Smirnov, The nature of channel constituents in hydrothermal synthetic emerald, Journal of Gemmology, 29 (2004) 215. [11] D.L. Wood and K. Nassau, Infrared spectra of foreign molecules in beryl, The Journal of Chemical Physics, 47 (1967) 2220. [12] B. Charoy, P. D. Donato, O. Barres, C. Pinto-Coelho, Channel occupancy in an alkali-poor beryl from Serra Branca (Goias, Brazil): Spectroscopic characterization, American Mineralogist, 81 (1996) 395. [13] C. Aurisicchio, O. Grubessi, P. Zecchini, Infrared spectroscopy and crystal chemistry of the beryl group, The Canadian Mineralogist, 32 (1994) 55. [14] A. M. Hofmeister, T.C. Hoering and D. Virgo, Vibrational spectroscopy of beryllium aluminosilicates: Heat-capacity calculations from band assignments, Physics and Chemistry of Minerals, 14 (1987) 205. [15] F. P. Stewart, K. Refson, R. I. Bewley and G. Dent, Assignment of the vibrational spectra of lithium hydroxide monohydrate, LiOH-H2O, The journal of chemical physics, 134 (2011). [16] D. M. Adams and I.R. Gardner, Single-crystal vibrational spectra of beryl and dioptase, Journal of the Chemical Society - Dalton Transactions, 1974 (1974) 1502. [17] Hawthorne F.C. and P. Černý, The alkali-metal positions in Cs-Li beryl, Canadian Mineralogist, 15 (1977) 414.